Lessons in sustainable development from Japan and South Korea - Hsu, Sara; Naoi, Michio; Zhang, Wenjie; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Lessons in Sustainable Development from Japan and South Korea compares the two countries, makes policy recommendations, and examines sustainable development experiments from both nations.
Keywords: Science